The GLP-1 Analogs Liraglutide and Semaglutide Reduce Atherosclerosis in ApoE−/− and LDLr−/− Mice by a Mechanism That Includes Inflammatory Pathways - Rakipovski, Günaj; Rolin, Bidda; Nøhr, Jane; Klewe, Ib; Frederiksen, Klaus S.; Augustin, Robert; Hecksher-Sørensen, Jacob; Ingvorsen, Camilla; Polex-Wolf, Joseph; Knudsen, Lotte Bjerre (JACC. Basic to translational science, 2018)
[Display omitted] •The GLP-1RAs liraglutide and semaglutide reduce cardiovascular risk in type 2 diabetes patients.•In ApoE−/− mice and LDLr−/− mice, liraglutide and semaglutide treatment significantly attenuated plaque lesion development, in part independently of body weight and cholesterol lowering.•Semaglutide decreased levels of plasma markers of systemic inflammation in an acute inflammation model (lipopolysaccharide), and transcriptomic analysis of aortic atherosclerotic tissue revealed that multiple inflammatory pathways were down-regulated by semaglutide. The glucagon-like peptide-1 receptor agonists (GLP-1RAs) liraglutide and semaglutide reduce cardiovascular risk in type 2 diabetes patients. The mode of action is suggested to occur through modified atherosclerotic progression. In this study, both of the compounds significantly attenuated plaque lesion development in apolipoprotein E-deficient (ApoE−/−) mice and low-density lipoprotein receptor-deficient (LDLr−/−) mice. This attenuation was partly independent of weight and cholesterol lowering. In aortic tissue, exposure to a Western diet alters expression of genes in pathways relevant to the pathogenesis of atherosclerosis, including leukocyte recruitment, leukocyte rolling, adhesion/extravasation, cholesterol metabolism, lipid-mediated signaling, extracellular matrix protein turnover, and plaque hemorrhage. Treatment with semaglutide significantly reversed these changes. These data suggest GLP-1RAs affect atherosclerosis through an anti-inflammatory mechanism.